Difference of serum tumor markers in different clinical stages of elderly patients with non-small cell lung cancer and evaluation of diagnostic value - Qin, WenWen; Wang, Ping; Ding, CuiMin; Peng, Fei (Journal of Medical Biochemistry, 2023)
Objective To explore the difference and diagnostic value evaluation of serum tumor markers in different clinical stages of elderly non-small cell lung cancer (NSCLC) patients. Methods Select 100 elderly NSCLC patients admitted to our hospital from June 2018 to June 2021, collect the general data, pathology data and imaging data of the patients, and the patients were divided into I-IV clinical stages according to the International Union Against Cancer (UICC) 8th edition lung cancer TNM staging standard. Detect the subjects’ peripheral serum tumor markers, serum carcinoembryonic antigen (CEA), cytokeratin fragment 21-1 (CYFRA21-1), squamous cell carcinoma-associated antigen (SCCA), carbohydrate antigen 125 (CA125) and sugar Class antigen 199 (CA199). Compare the differences of serum CEA, CYFRA21-1, SCCA, CA125, CA199 levels in different clinical stages of elderly NSCLC patients, and the diagnostic value of the above indicators for elderly NSCLC patients was analyzed by receiver operating characteristic curve (ROC curve) and area under the curve (AUC). Results The smoking history, differentiation degree, lymph node metastasis and tumor diameter of elderly NSCLC patients with different clinical stages are significantly different; with the increase of NSCLC disease progression, the levels of serum CEA, CYFRA21-1, SCCA, CA125, and CA199 continue to increase, and serum tumors There is a significant correlation between the markers; serum CEA, CYFRA21-1, SCCA, CA125, CA199 have diagnostic value for the clinical staging of elderly NSCLC patients. Conclusions The elevation of serum CEA, CYFRA21-1, SCCA, CA125 and CA199 in elderly NSCLC patients is positively correlated with the degree of tumor malignancy. The detection of the above indicators is of great value for the early diagnosis and disease monitoring of elderly NSCLC.